2007
DOI: 10.1002/jor.20487
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of suppressed metabolism in prolonged cold preserved cartilage

Abstract: Chondrocytes in cold preserved cartilage are metabolically suppressed. The goal of this study was to address this metabolic suppression and seek ways to reverse it. Specifically, we examined the roles of rewarming protocols and nitric oxide (NO) in this metabolic suppression. Bovine and canine full-thickness articular cartilage explants were cultured under various temperature conditions, and NO production, proteoglycan (PG) synthesis, and cell viability were measured. Nitric oxide was shown to be negatively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
(56 reference statements)
0
9
1
Order By: Relevance
“…For this reason, it is important to understand the implications of this cold storage on the molecular environment in the specimens, because a prolonged storage at the refrigerator temperature can change the tissue/cell properties in many ways [811]. In clinical treatment of large joint defects in humans, fresh osteochondral allograft transplantation is a well-established technique [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is important to understand the implications of this cold storage on the molecular environment in the specimens, because a prolonged storage at the refrigerator temperature can change the tissue/cell properties in many ways [811]. In clinical treatment of large joint defects in humans, fresh osteochondral allograft transplantation is a well-established technique [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…16 The published clinical studies reflect the situation where grafts were harvested, stored in lactated Ringer's solution at 48C, and transplanted between 2 and 5 days from the time of harvest. 17,18 However, although the viability of cold-preserved articular cartilage is significantly diminished within 1 week, [19][20][21] appropriate serology testing to minimize the chances for the disease transmission requires a minimum of 2 weeks. 16 In this study, a storage solution containing EGCG was used to test the hypothesis that cold preservation injury of articular cartilages can be prevented by EGCG-mediated reversible regulation of cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…ROS thus have an adverse effect on articular cartilage storage. Previous studies of organ and tissue preservation also demonstrated that ROS were generated during cold preservation and rewarming (Bartels-Stringer et al 2003;Pylawka et al 2008;Rauen and de Groot 1998). In the present study, therefore, the reason why chondrocyte deformity was observed in the deep layer of articular cartilage may be that ROS were generated there, promoted by the cold environment and subsequent rewarming.…”
Section: Discussionmentioning
confidence: 55%